Encyclopedia of genetics, genomics, proteomics, and informatics: VOL.1 - Rédei, George P (Springer, 2008)
This new third edition updates a best-selling encyclopedia. It includes about 56% more words than the 1,392-page second edition of 2003. The number of illustrations increased to almost 2,000 and their quality has improved by design and four colors.